2005
DOI: 10.1152/ajpregu.00762.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cardiovascular effects of nociceptin microinjected into the nucleus tractus solitarius of the rat

Abstract: .62, and 1.25 mmol/l of nociceptin into the medial nucleus tractus solitarius (mNTS) elicited decreases in mean arterial pressure (11 Ϯ 1.8, 20 Ϯ 2.1, 21.5 Ϯ 3.1, and 15.5 Ϯ 1.9 mmHg, respectively) and heart rate (14 Ϯ 2.7, 29 Ϯ 5.5, 39 Ϯ 5.2, and 17.5 Ϯ 3.1 beats/min, respectively). Because maximal responses were elicited by microinjections of 0.62 mmol/l nociceptin, this concentration was used for other experiments. Repeated microinjections of nociceptin (0.62 mmol/l) into the mNTS, at 20-min intervals, did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 31 publications
4
18
1
Order By: Relevance
“…The mNTS sites eliciting depressor and bradycardic responses were identified by microinjections of L-Glu (5 mM) (8,39). The volume of all microinjections into the mNTS was 100 nl; the selection of this volume was based on our previous study (6). The volumes were pressure ejected and visually confirmed by the displacement of fluid meniscus in the barrel containing the solution using a modified binocular horizontal microscope with a graduated reticule in one eye piece.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mNTS sites eliciting depressor and bradycardic responses were identified by microinjections of L-Glu (5 mM) (8,39). The volume of all microinjections into the mNTS was 100 nl; the selection of this volume was based on our previous study (6). The volumes were pressure ejected and visually confirmed by the displacement of fluid meniscus in the barrel containing the solution using a modified binocular horizontal microscope with a graduated reticule in one eye piece.…”
Section: Methodsmentioning
confidence: 99%
“…immunoreactive for ANG- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) has been demonstrated in the nucleus tractus solitarius (NTS) of the rat (1,24). It has recently been reported that bilateral microinjections of ANG- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) into the NTS attenuate the bradycardic responses to intravenous injections of phenylephrine (PE) (1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The following doses of the drugs were used: Kyn, 0.15 to 5 nmol/50 nL; AP5, 0.16 to 1.4 nmol/50 nL; CNQX, 0.22 to 1.8 nmol/50 nL; and gabazine, 0.3 to 10 nmol/50 nL. The microinjection doses for Kyn, 15,27 AP5, 15 CNQX, 29 and gabazine 30,31 were selected from previous studies and tested in the pilot experiments.…”
Section: Pvn Microinjectionsmentioning
confidence: 99%